Learning from the past: old and new ksour in the M’Zab Valley (Algeria) - Azil, Cheima; Vicario, Margherita (Restauro Archeologico, 2023)
Most World Heritage Sites in the Maghreb region are threatened by numerous natural and anthropic hazards, the latter usually due to complex economic, social and cultural dynamics. Because of changes in ways of life and housing models, traditional building cultures are often not recognised by inhabitants as heritage and are becoming unable to resist the spread of modern standardised technologies. These changes put at risk the conservation status and consequently the Outstanding Universal Value of the sites. The World Heritage Site of the M’Zab Valley in Algerian desert is a rare example of the preservation of both tangible and intangible dimensions of heritage and their transmission to new generations through the construction of the new settlement of Tafilalt, built interpreting the traditional techniques. The contribution analyses the case of the M’Zab Valley in order to show the role of community involvement in safeguarding the authenticity and integrity of this World Heritage Site.